Geological and genetic modelling of the Cenozoic deposits of the Brest region using information technologies - Mayeuskaya, Hanna M.; Bahdasarau, Maksim A.; Piatrou, Dzmitry A.; Sheshka, Mikalai M. (Journal of the Belarusian State University. Geography and Geology, 2023)
The general principles of using information technologies to create a geological and genetic model of the Cenozoic deposits of the territory of the Brest region, as a stratum with practical potential for the development and forecasting of new deposits of mineral raw materials in the region, are disclosed. The relevance of the work lies in the creation of the first digital geological and genetic model of the region based on the most complete geological drilling materials, which made it possible to increase the productivity of working with the available geological exploration data (in comparison with the previously used manual processing), to detail the features of the structure of the Cenozoic strata of the study area, to establish its prospects for the growth of new deposits of common minerals, and to form a series of digital maps reflecting the spatial localisation of the identified deposits of non-metallic raw materials. It is assumed that the created model, on the one hand, will allow geologists to plan further exploration of the subsoil of the region for the development of its mineral resource base, on the other hand, it will serve as a qualitative basis for providing interested organisations with information about promising deposits of common minerals in the region. The procedure for implementing the model according to the proposed methodology included six successive stages (from preliminary data processing to verification of the results obtained) and provided for the creation of a model in volumetric form (due to the multilayer structure of the geological data used), as well as its transformation into a two-dimensional format (which is the most accessible for analysis by interested organisations). The results obtained in the course of modelling and presented in the form of several examples in this paper show the effectiveness of the proposed methodology, which can later be used when conducting studies similar to this one in other regions of Belarus.
Keywords: Brest region; Cenozoic deposits; geological and genetic model; information technology; digital maps; common minerals